Upaya Meningkatkan Kemampuan Siswa Kelas II SD Islam Terpadu Harun Ar-Rasyid Picung Kabupaten Pandeglang dalam Menghafal Al-Qur’an dengan menggunakan Metode One Day One Ayat - Ela Hikmah Hayati; Euis Ernawati; Neng Elva; Nurul Fatimah (CV. Creative Tugu Pena, 2024)
The aim of this research is to determine efforts to improve the ability of Class II students at Harun Ar-Rasyid Picung Integrated Islamic Elementary School, Pandeglang Regency in memorizing the Al-Qur'an using the one day one verse method for the 2022/2023 academic year. The method in this research is using Classroom Action Research which is carried out in 3 cycles. Each cycle includes planning, action, observation and reflection. Data collection techniques were carried out by means of observation, interviews and documentation. In testing the validity of the data, triangulation of sources and methods was used. Then the data was analyzed using an interactive analysis model with the steps: data collection, data reduction, data presentation, and drawing conclusions. The results of this research indicate that efforts to improve the ability to memorize the Al-Qur'an for class II students are carried out by: 1) Creating a pleasant atmosphere when teaching and learning in class, 2) Providing time for students who want to memorize them, 3) Muroja'ah surah juz 30 which is the target for students to memorize, 4) Providing motivation to students, 5) Providing additional lesson hours for Tahfizul Qur'an, 6) Creating a WA group for parents of students, 7) Coordinating with the school principal.